2016
DOI: 10.1002/cjce.22604
|View full text |Cite
|
Sign up to set email alerts
|

Removal of nitric oxide in a microporous tube‐in‐tube microchannel reactor by ferrous chelate solution

Abstract: NO gas emission has harmfully impacted human health and the environment. Absorption of NO gas into an aqueous solution is considered to be a promising approach for its removal. FeII(EDTA) solution has been demonstrated as an efficient option in the denitrification process. However, its absorption rate is strongly affected by mass transfer limitation of NO into FeII(EDTA) solution in traditional reactors. In this paper, the removal process of NO with FeII(EDTA) solution was studied in a microporous tube‐in‐tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…If the flow rate ratio (R) is increased (reduction of Q B ), to maintain a balanced stoichiometric ratio, the concentration of acid ([H + ] 0 ) should be increased. In other words, it needs to keep a fixed amount for n A n B in Equation (5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the flow rate ratio (R) is increased (reduction of Q B ), to maintain a balanced stoichiometric ratio, the concentration of acid ([H + ] 0 ) should be increased. In other words, it needs to keep a fixed amount for n A n B in Equation (5).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] So, micro-technology is currently applied as a fine area for rapid development in numerous applications due to great mass transfer and efficiency of mixing, high product selectivity, safety proficiency, and lower energy usage. [4][5][6][7][8] Indeed, microreactors perform continuous chemical reactions in a micro-scale channel and provide a highly specific surface. Moreover, microreactors are normally three-dimensional configurations with an inner diameter of less than a millimetre, and reaction capacities in the nanolitre to microlitre limits.…”
Section: Introductionmentioning
confidence: 99%
“…He et al , reported that the reduction reaction between reducing metals and Fe II (EDTA)–NO was an endothermic process, suggesting that high temperature was beneficial to Fe II (EDTA)–NO reduction. However, according to Henry’s law, excessive temperature would reduce the solubility of NO in the absorbent solution, which may result in secondary pollution. Thus, temperature is one of the significant factors on Fe II (EDTA)–NO reduction.…”
Section: Results and Discussionmentioning
confidence: 99%